2014
DOI: 10.1038/npp.2014.135
|View full text |Cite
|
Sign up to set email alerts
|

Rat Nucleus Accumbens Core Astrocytes Modulate Reward and the Motivation to Self-Administer Ethanol after Abstinence

Abstract: Our understanding of the active role that astrocytes play in modulating neuronal function and behavior is rapidly expanding, but little is known about the role that astrocytes may play in drug-seeking behavior for commonly abused substances. Given that the nucleus accumbens is critically involved in substance abuse and motivation, we sought to determine whether nucleus accumbens astrocytes influence the motivation to self-administer ethanol following abstinence. We found that the packing density of astrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 61 publications
(82 reference statements)
4
109
0
1
Order By: Relevance
“…3D). Consistent with a Gq mechanism and the recent report that GFAP driven Gq DREADD activation elevated [Ca 2+ ] i in astroglia (34), these data indicate that CNO-mediated release of glutamate relies on internal Ca 2+ stores. Also consistent with this interpretation, previous reports show minor involvement of plasmalemmal Ca 2+ channel conductances on vescicular glial glutamate release (13, 35).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…3D). Consistent with a Gq mechanism and the recent report that GFAP driven Gq DREADD activation elevated [Ca 2+ ] i in astroglia (34), these data indicate that CNO-mediated release of glutamate relies on internal Ca 2+ stores. Also consistent with this interpretation, previous reports show minor involvement of plasmalemmal Ca 2+ channel conductances on vescicular glial glutamate release (13, 35).…”
Section: Resultssupporting
confidence: 88%
“…6). Further supporting an involvement of glutamate gliotransmission in the regulation of addictive behavior, a recent report from the Bowers lab demonstrated that stimulating glial Gq-DREADD in the NAcore inhibited the motivation to seek ethanol (34). While we used cell morphology and characteristics of glutamate release by CNO (dnSNARE mice and relative insensitivity to N-channel blockers) to show that Gq-DREADD was expressed in glia, a very minor contribution by neuronal Gq-DREADD cannot be 100% ruled out.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Bull et al (2014) demonstrate that activation of Gq signaling with the hM3D DREADD in NAcore astrocytes enhances internal calcium concentration, facilitates intracranial self-stimulation, and reduces motivation to seek ethanol after 3 weeks of abstinence. Furthermore, activation of astroglial Gq-DREADD promotes glutamate release and inhibits cue-induced cocaine seeking, likely through restoration of glutamate tone on mGluR2/3 receptors in the NAcore similar to what is described above for NAC .…”
Section: G Glial Modulatorsmentioning
confidence: 82%
“…Since then, hM3Dq has been widely used to enhance neuronal firing, and I here cite only representative examples in which feeding (Krashes et al, 2011; Atasoy et al, 2012), energy expenditure (Kong et al, 2012), locomotion and striatal synaptogenesis (Kozorovitskiy et al, 2012), memory (Garner et al, 2012), and social behaviors (Peñagarikano et al, 2015) have been modulated by hM3Dq in vivo. Because hM3Dq activation induces intracellular calcium release, it has also been used to “activate” astrocytes (Agulhon et al, 2013; Bull et al, 2014; Scofield et al, 2015), hepatocytes (Li et al, 2013), pancreatic ÎČcells (Guettier et al, 2009; Jain et al, 2013), vascular smooth muscle cells (Armbruster et al, 2007), and iPS-derived neuroblasts (Dell’Anno et al, 2014). …”
Section: Current Dreaddsmentioning
confidence: 99%